Analisis Kesulitan Mahasiswa Pendidikan Matematika dalam Menyelesaikan Masalah Pembuktian Pernyataan Matematika - Suwanti, Vivi; Fayeldi, Trija (Jurnal Tadris Matematika, 2018)
This study’s aim is to describe mathematics education college students difficulties when doing mathematical proof. This study employs descriptive qualitative methods. This study subjects are 3 mathematic education college students who take real analysis class. The subjects was chosen according to their mathematics proposition proof ability in real analysis. The study was carried out by two step tests, they are written and oral test. Based on the study results we know that: college student with high ability tends to have difficulty in write the information that used to proof in written form, but they still manage to get the right proof; college student with middle ability tends to have difficulty in construct the suitable steps and logics to proof the proposition; and college student with low ability tends to have difficulty in understanding the purpose, meaning, and properties that given by the known proposition in the task. In order to deepen this study results, in the next study, we can employs a standard method to detects difficulty, such as NEA (Newton’s Error Analysis), to find more structured results.